# ISI2014-DCG-49

0 votes
84 views

Let $f(x) = \dfrac{x}{(x-1)(2x+3)}$, where $x>1$. Then the $4^{th}$ derivative of $f, \: f^{(4)} (x)$ is equal to

1. $- \frac{24}{5} \bigg[ \frac{1}{(x-1)^5} – \frac{48}{(2x+3)^5} \bigg]$
2. $\frac{24}{5} \bigg[ – \frac{1}{(x-1)^5} + \frac{48}{(2x-3)^5} \bigg]$
3. $\frac{24}{5} \bigg[ \frac{1}{(x-1)^5} + \frac{48}{(2x+3)^5} \bigg]$
4. $\frac{64}{5} \bigg[ \frac{1}{(x-1)^5} + \frac{48}{(2x+3)^5} \bigg]$
in Others
retagged
0
3

@JEET

use partial fraction.

$\frac{x}{(x-1)(2x+3)} = \frac{A}{(x-1)} + \frac{B}{(2x+3)}$

$\Rightarrow x = A(2x+3) + B(x-1)$

when $x=1$, then $1=5A$ i.e. $A= 1/5$

when $x=-3/2$, then $-3/2=-5B/2$ i.e. $B= 3/5$

So, $f(x) = \frac{x}{(x-1)(2x+3)} = \frac{1}{5(x-1)} + \frac{3}{5(2x+3)}$

now, successive differentiation will be easy :)

1
Thanks.
0

@ankitgupta.1729

I am not getting this 48 in the differentiation of $\frac{3}{5(2x+3)}$.

Can you please verify once??

2

@JEET

Here, $f(x) = \frac{1}{5(x-1)} + \frac{3}{5(2x+3)}\\ f'(x) =\frac{-1}{5(x-1)^2} - \frac{6}{5(2x+3)^2}\\ f''(x) = \frac{2}{5(x-1)^3} + \frac{24}{5(2x+3)^3}\\ f'''(x) = \frac{-6}{5(x-1)^4} - \frac{72*2}{5(2x+3)^4} \\f''''(x) = \frac{24}{5(x-1)^5} + \frac{72*2*8}{5(2x+3)^5}$

answer should be (C)

1
I made a foolish mistake. I wasn't differentiating the $2x$ itself.

Between thanks.

## 1 Answer

1 vote

Answer: $\mathbf C$

Explanation:

Using partial differentiation:

$\frac{x}{(x-1)(2x+3)} = \frac{\mathrm A}{x-1} + \frac{\mathrm B}{(2x+3)}$

$\Rightarrow \mathrm x = \mathrm A(2x+3) + \mathrm B(x-1)$

When $x = 1$, then $1 = 5\mathrm A \Rightarrow \mathrm A = \frac{1}{5}$

when $x = -\frac{3}{2}, \text {then}\; -\frac{3}{2} = -\frac{5\mathrm B}{2} \Rightarrow \mathrm B = \frac{3}{5}$

So, $f(x) = \frac{x}{(x-1)(2x+3)} = \frac{1}{(x-1)}+\frac{3}{5(3x+3)}$

Now, $f(x) = \frac{1}{5(x-1)} + \frac{3}{5(2x+3)}\\ f'(x) =\frac{-1}{5(x-1)^2} - \frac{6}{5(2x+3)^2}\\ f''(x) = \frac{2}{5(x-1)^3}+ + \frac{24}{5(2x+3)^3}\\ f'''(x) = \frac{-6}{5(x-1)^4} - \frac{72\times2}{5(2x+3)^4} \\f''''(x) = \frac{24}{5(x-1)^5} + \frac{72\times2\times8}{5(2x+3)^5} \\f''''(x) = \frac{24}{5}\bigg[\frac{1}{(x-1)^5} + \frac{48}{5(2x+3)^5}\bigg ]$

$\therefore \mathrm {\mathbf C}$ is the correct option.

edited by
1
Can you make another line to show the closed form like those in the options?

I meant to show
$=\frac{24}{5} \bigg[ \frac{1}{(x-1)^5} + \frac{48}{(2x+3)^5} \bigg]$ being the last line.
1
Done!

Thanks for pointing out.

## Related questions

2 votes
1 answer
1
114 views
Let the function $f(x)$ be defined as $f(x)=\mid x-1 \mid + \mid x-2 \:\mid$. Then which of the following statements is true? $f(x)$ is differentiable at $x=1$ $f(x)$ is differentiable at $x=2$ $f(x)$ is differentiable at $x=1$ but not at $x=2$ none of the above
0 votes
1 answer
2
117 views
If $f(x) = \sin \bigg( \dfrac{1}{x^2+1} \bigg),$ then $f(x)$ is continuous at $x=0$, but not differentiable at $x=0$ $f(x)$ is differentiable at $x=0$, and $f’(0) \neq 0$ $f(x)$ is differentiable at $x=0$, and $f’(0) = 0$ None of the above
2 votes
2 answers
3
145 views
If $f(x)$ is a real valued function such that $2f(x)+3f(-x)=15-4x$, for every $x \in \mathbb{R}$, then $f(2)$ is $-15$ $22$ $11$ $0$
2 votes
3 answers
4
102 views
If $f(x) = \dfrac{\sqrt{3} \sin x}{2+\cos x}$, then the range of $f(x)$ is the interval $[-1 , \sqrt{3}{/2}]$ the interval $[-\sqrt{3}{/2}, 1]$ the interval $[-1, 1]$ none of these